SPECIFIC FEATURES OF TRANSLATION OF TEXTS RELATED TO OIL AND GAS INDUSTRY - Norova , Sarvinoz Karimovna (Innovative Development in Educational Activities, 2023)
This paper discusses the theoretical and methodological issues of translating words related to oil and gas industry.